Organizational structure of the legal profession in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2021)
Today, improving the means of protecting human rights is not only an integral part of the overall process of forming the rule of law, but also a prerequisite for determining the degree of maturity of civil society. That is why understanding the nature of the legal profession, its types, forms of organization, areas of activity, relationships with other social structures and the legal regulation of its existence is the essence of scientific research about the legal profession. The relevance of the topic of the article is confirmed by the trends and dynamics of the internal development of modern democratic states, the need for a comprehensive comprehensive theoretical and legal study of the effectiveness of the bar in the mechanism of ensuring the constitutional rights of citizens, the creation of a conceptual model of the new relationship of the bar with state authorities, civil society, The article considers the organizational structure of the bar under the Law of the Republic of Kazakhstan “On Advocacy and Legal Assistance”. Legal practice in the Republic of Kazakhstan is organized in a legal consultation established by the bar association, or by creating a law office by lawyers who carry out sole activity without registration of a legal entity, as well as independently or jointly with other lawyers. The article focuses on the peculiarities of the organization of these forms of organization of the bar, as well as the features of the activities of the Republican bar association, the body of management of the bar at the republican level. The article highlights the best foreign practices and activities of the International Bar Association.Key words: legal profession, bar association, legal practice, legal advice, legal assistance, client, attorney-client privilege, law office.